2022
DOI: 10.3389/fcimb.2022.977157
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of estrogen on Candida albicans hyphal cell wall glycans and ergosterol synthesis

Abstract: Increased levels of 17-β estradiol (E2) due to pregnancy in young women or to hormonal replacement therapy in postmenopausal women have long been associated with an increased risk of yeast infections. Nevertheless, the effect underlying the role of E2 in Candida albicans infections is not well understood. To address this issue, functional, transcriptomic, and metabolomic analyses were performed on C. albicans cells subjected to temperature and serum induction in the presence or absence of E2. Increased filamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Metabolomics has been applied to many fields of research, including studies in non-communicable and infectious diseases. ( Cacciatore and Loda, 2015 ; Vignoli et al, 2020 ; Bataineh et al, 2022 ), molecular biology ( Semreen et al, 2020 ; AL Bataineh et al, 2021 ), and food research ( Maccaferri et al, 2012 ; Ojo-Okunola et al, 2020 ). In the medical field, it has played a key role in enhancing research in personalized medicine ( Cacciatore et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has been applied to many fields of research, including studies in non-communicable and infectious diseases. ( Cacciatore and Loda, 2015 ; Vignoli et al, 2020 ; Bataineh et al, 2022 ), molecular biology ( Semreen et al, 2020 ; AL Bataineh et al, 2021 ), and food research ( Maccaferri et al, 2012 ; Ojo-Okunola et al, 2020 ). In the medical field, it has played a key role in enhancing research in personalized medicine ( Cacciatore et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multi-omics analysis has made a major contribution to the field of medical microbiology [35][36][37][38], specifically liquid chromatography-mass spectrometry-based, and proteomics/metabolomics approaches have provided the research community with key molecular and cellular elements that provide a comprehensive understanding of microbial system biology and important aspects of microbial physiology [35,36,39]. Of note, until now, most of the multi-omics studies performed on C. albicans were performed in liquid media, which has been, beyond any doubt, a valuable contribution to this research field (e.g., [40][41][42][43][44]).…”
Section: Multi-omics Approach In Microorganismsmentioning
confidence: 99%
“…The top 5 potential metabolites with the highest VIP scores were identified as Spironolactone, Ile-Ser-Leu, Tsangane L 3-glucoside, 1-Methyluric acid, and Val-Ile-Ile. Spironolactone is a steroid lactone, and existing research has demonstrated the impact of steroid hormones on fungal growth [59][60][61][62], morphology [63,64], and virulence [65,66]. Specifically, steroids disrupt fungal cell wall-or membrane-specific sensor proteins, leading to membrane stretching and activation of the CWI pathway [67,68].…”
Section: Impact Of Potential Key Metabolites On Growth and Pathogenic...mentioning
confidence: 99%